Analysis of Quality of Service in VANET. Issue 1 (December 2020) - Srivastava, Akshat; Verma, Sahil; Kavita; Jhanjhi, NZ; Talib, M N; Malhotra, Atul
Abstract: VANET as Inter-vehicle communication is becoming a promising area of research, standardization, and growth with the ever-growing number of vehicles equipped with computer technology and wireless communication tools. Due to its erratic portability and the interrupted availability of a network, VANET is relatively incomprehensible for a strong end to end communication, In Vehicular Network the main advantage is that it communicates by using nodes. Because of its simple and basic method of communication, MANET is used most often in the military, just like data sharing between different computers. VANET and some modifications are identical to MANET. VANET encompass the mobile nodes which are indicated as (MN), The vehicle networking system has drawn significant interest from academia and industry since its establishment. Its technology is used for military purposes by several foreign manufacturing and government sectors, it also enables a wide range of applications, including collision prevention, security, blind crossing, dynamic route planning, traffic condition monitoring on a real-time basis, etc but there are certain loopholes or drawbacks like frequent network drop, high mobility which affected the overall QoS, In this paper, there are brief analyses on Quality of Service which include certain Routing Protocol like DIVERT, FBAODV, DSR and also to decrease the congestion control, there is a comparative study of the different protocol which evaluates in increasing the throughput and network efficiency.